Insight into decision of marriage by late teens and early-twenties women in Dhaka middle class: their agency, respectability and role of external factors - Sharar, Raad (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2018.